2021
DOI: 10.1049/rsn2.12070
|View full text |Cite
|
Sign up to set email alerts
|

Research on main‐lobe deceptive jamming against FDA‐MIMO radar

Abstract: A multiple‐input multiple‐output (MIMO) radar with frequency diverse array (FDA) produces a range‐angle‐dependent steering vector, which can suppress the deceptive jamming in joint range‐angle domain. This in turn complicates the task of radar jamming. With the emergence and development of digital radio frequency memory (DRFM), radar electronic jamming technique has entered the age of coherent jamming. Based on the analysis of the superiority of the FDA‐MIMO radar in cancelling the deceptive jammers, a novel r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The current tracking radar countermeasures tend to use deception jamming because the active emission of a high-power noise jamming signal can be very easily traced and combated. The existing track deception jamming techniques implemented by DRFM have suffered from a low number and fidelity of false targets [5][6][7]. These methods require that the incident signal be intercepted, followed by the analysis and calculation of the corresponding jamming signal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current tracking radar countermeasures tend to use deception jamming because the active emission of a high-power noise jamming signal can be very easily traced and combated. The existing track deception jamming techniques implemented by DRFM have suffered from a low number and fidelity of false targets [5][6][7]. These methods require that the incident signal be intercepted, followed by the analysis and calculation of the corresponding jamming signal.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the current study is that the actual effect has not been demonstrated experimentally at present; we aim to focus on this in future research. In addition, the false tracks generated by this method were limited to the distance dimension, and distanceazimuth two-dimensional deception has yet to be achieved [5][6][7]. In existing studies, PSS has shown more severe restrictions on the angle and frequency of the incident signal in practical experiments, which is one of the reasons why PSS material design is more popular.…”
Section: Analysis Of Deception Effect With Different Number Of Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] and gained substantial attention from researchers due to its flexible beam scanning characteristic [3][4][5][6][7][8][9]. By employing a tiny frequency offset across adjacent array elements, the FDA can provide a time-range-angle-dependent beampattern, which makes it possible to suppress the rangedependent clutter or main-lobe interference through a proper beamforming method [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the effect of time delay, the FDA deceptive jamming model is rederived in [21]. The deceptive interference signal flow is corrected in [22,23], and a new range dimension deceptive interference method is proposed. Yang Chen [24] proposed a composite interference method of suppression and range deception for FDA-MIMO beamforming.…”
Section: Introductionmentioning
confidence: 99%